PENERAPAN FIQIH MUAMALAH SEBAGAI DASAR KEWENANGAN PENGADILAN AGAMA DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH - Supriyatni, Hj. Renny (Syiar Hukum, 2010)
he development of Islamic economic institutions in Indonesia has created the conflict of interest between Â stakeholder and Â Religious Court, especially in settlement of syariah-economic disputes. The Â application of fiqih muamalah in settlement of syariah-economic disputes in Islamic Religious Court, Â has been the crucial issue in Indonesia positive law . This article will seek to find and determine Â whether the application of Â fiqih muamalah as a basis in such dispute settlement is consistent with Â the Islamic Law Principles. It also examines the implementation of Â fikih muamalah that has become an Indonesian postive law. This research applies juridical normative approach. Â Data collection Â is gathered from library research complemented by primary from field research. The specification of this research is descriptive analysis, and the data gathered Â is analyzed in qualitative method. Â The article will demonstrate that Â the above fiqih muamalah rules are stipulated in Law No.3 of 2006 Â Jo. Law No 50 of 2009 on Â Second Amendment of Act No.7 of 1989. Â Meanwhile, the Islamic Law Principles have been adopted by Law No.21 of 2008, Â the Supremre Court Decree No 2 of 2008 and other relevant laws and regulations. The author Â recommends that the Indonesian Government adopt implementing regulation on syariah- economic. Â It is also recommended that the government Â should enhance socialization of the laws and regulations relating to fikih muamalah and syariah âeconomic Â to the general public. Â  This can be a Â guidance for the Indonesian Muslims to comprehensively practice Â their religion teaching.